Rabies in the insectivorous bat Tadarida brasiliensis in Southeastern Brazil - Wilson Uieda
This is the first recorded case of rabies in the insectivorous bat Tadarida brasiliensis in the State of S. Paulo, Southeastern Brazil. The infected bat was found in the afternoon while hanging on the internal wall of an urban building. This observation reinforces the notion as to the caution one must exercise regarding bats found in unusual situations.